Innovative Strategies in Physical Education Learning in the Digital Era in Mataram City - Lalu Taufan Ali Gufran; Nguyen Thi Lan (SEED: Journal of Scientific Research, 2025)
The digital era has brought significant changes in various aspects of life, including in the field of education. Physical Education, as a subject that plays an important role in students' physical, mental and social development, needs to adopt innovative strategies to remain relevant and effective. This article discusses various innovative strategies in Physical Education learning that utilize digital technology, such as fitness applications, video tutorials, gamification, and virtual-based learning. This approach not only increases student engagement but also allows for more flexible and personalized learning. The results of the analysis show that the use of digital technology can increase student motivation, expand access to learning resources, and make it easier for teachers to measure and evaluate student development. However, challenges such as lack of digital literacy among teachers and students, limited technological facilities, and potential risks of technology use such as screen addiction need to be addressed through training, providing infrastructure, and a balanced learning approach. This article emphasizes the importance of collaboration between educators, parents, and policy makers in supporting the implementation of innovative strategies in Physical Education. In this way, it is hoped that Physical Education learning can continue to adapt and make a significant contribution to student development in the digital era.